(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article analyzes the problem of formation of religious (moral) values o f the personality in adolescence. The concept of religious values a s a basis for the moral principles of society is considered. Examples of methods for studying religious (moral) values a re given. The results of diagnostics of the level of formation of religious (moral) values a re presented. The difference between the results of the research between the tested groups of adolescents is demonstrated. The influence of religious teaching on the formation of moral values in adolescence is described. The methods of educational influence on introduction of religious education are offered.